Evaluation of sexual function in sexually active women 1 year after transvaginal NOTES: a prospective cohort study of 106 patients - Linke, Georg R.; Warschkow, René (Langenbeck's archives of surgery, 2013)
PurposeThe primary objective of this prospective cohort study was to investigate sexual function, quality of life and patient satisfaction in sexually active women 1 year after transvaginal hybrid natural orifice transluminal endoscopic surgery (NOTES).Patients and methodsThis prospective single-centre cohort study included sexually active female patients after transvaginal hybrid NOTES cholecystectomy or anterior resection. Sexual life impairment and quality of life were assessed by the Gastrointestinal Quality of Life Index (GIQLI) prior and 1 year after surgery. Patient satisfaction was assessed as well as the sexual function 1 year postoperatively using the validated German version of the Female Sexual Function Index (FSFI-D).ResultsBetween September 2008 and December 2009, 106 sexually active women after transvaginal hybrid NOTES cholecystectomy or anterior resection were identified. Sexual life significantly improved (GIQLI scores 3.2 ± 1.0 preoperatively vs. 3.7 ± 0.7 1 year postoperatively, P < 0.001), and painful sexual intercourse (3.3 ± 1.0 vs. 3.6 ± 0.7, P = 0.008) decreased post-surgery. The mean FSFI-D total score after transvaginal NOTES was 28.1 ± 4.6, exceeding the cutoff for sexual dysfunction defined as 26. Four (4.5 %) out of 88 patients who answered this question were not satisfied with the transvaginal hybrid NOTES procedure.ConclusionsThis prospective cohort study of female sexual function after transvaginal NOTES provides compelling evidence that the transvaginal access is safe and associated with high satisfaction rate.
First online: 26 August 2012
Gesehen am 19.11.2018